PHYSICAL ACTIVITY AND SPORTS IN PATIENTS WITH EPILEPSY - Odintsova, G.V.; Koloteva, A.V.; Lovyagina, A.E. (Malang Neurology Journal, 2020)
Background: For many years, patients with epilepsy have been strongly advised to avoid sports and exercise, as it was believed that sporting activities can trigger seizures.Objective: To study the level of physical and sporting activity on the example of the patients of the Russian Epilepsy Center.Methods: The study includes 50 patients with a verified diagnosis of epilepsy. The survey has been conducted according to a specially developed questionnaire "Peculiarities of physical activity in patients with epilepsy", clinical and demographic study.Results: The average age is 29.6 years +/- 8.3. 57.2% of patients had restrictions on physical activity at school due to epilepsy. Motor activity was assessed as low by 12% of patients, as average — by 60%, as high — by 28%.Conclusion: Physical activity of patients with epilepsy remains insufficient due to medical and social restrictions. In most cases, physical activity and sports do not trigger seizures and worsening of the disease. Expansion of sports opportunities will improve social adaptation and reduce stigmatization with epilepsy. A differentiated approach to the definition of indications for sports and the engagement of a neurologist to determine contraindications are necessary.